1989
DOI: 10.1093/ajcn/49.4.708
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits and incidence of noninsulin-dependent diabetes mellitus in a population study of women in Gothenburg, Sweden

Abstract: Dietary intake as initially estimated in a cross-sectional study has been related to the 12-y incidence of diabetes mellitus in a prospective study of 1462 women. In addition, all 50-y-old women (n = 352) were subjected to an intravenous glucose tolerance test. Because of the sampling procedure and a high participation rate the participants were representative of middle-aged women in the general population. No differences of statistical significance were observed concerning intake of energy and different nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 12 publications
3
49
0
1
Order By: Relevance
“…Meat is an important source of total and saturated fat and could increase the risk of type 2 diabetes through overweight/obesity [41][42][43][44], the metabolic syndrome [45][46][47] and hyperinsulinaemia and hyperglycaemia [20, [48][49][50], although some studies found no association [51,52]. Another possible mechanism may be through the effects of haem-iron derived from meat [19,24,39,53].…”
Section: Discussionmentioning
confidence: 99%
“…Meat is an important source of total and saturated fat and could increase the risk of type 2 diabetes through overweight/obesity [41][42][43][44], the metabolic syndrome [45][46][47] and hyperinsulinaemia and hyperglycaemia [20, [48][49][50], although some studies found no association [51,52]. Another possible mechanism may be through the effects of haem-iron derived from meat [19,24,39,53].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional analysis of dietary intake supports the hypothesis that a low carbohydrate/high fat diet is associated with the onset of NIDDM (187). However, this evidence is not supported by prospective studies where dietary habits have been related to the development of NIDDM (188,189). The effects of a high carbohydrate diet on glucose tolerance have been equivocal (190,191).…”
Section: Exercise In the Treatment Of Glucose Intolerance And Niddmmentioning
confidence: 98%
“…The impact of dietary fat on the pathogenesis of NIDDM has been examined thoroughly in animal and short-term metabolic studies, which show that fat, and especially saturated fat, increases insulin resistance and hyperglycemia (Clandinin et al, 1993;Storlien et al, 1993;Roden et al, 1996) but long-term studies in men and women have been far less conclusive (Schwab et al, 1993;Swinburn, 1993;Hannah and Howard, 1994). In The San Luis Valley Diabetes Study, total fat and saturated fat intake were predictive of NIDDM, (Marshall et al, 1994) whereas prospective studies have not found similar associations (Snowden and Phillips, 1985;Feskens and Kromhout, 1989;Lundgren et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In the 30-year follow-up survey from the Dutch and Finnish male cohorts of the Seven Countries Study, ®sh, potatoes, vegetables and legumes appeared to protect against NIDDM (Feskens et al, 1995), but in a Swedish prospective study of women with imparied glucose tolerance, no association was found between foods or macronutrients and the development of NIDDM (Lundgren et al, 1989). Thus, we have only little present knowledge about the potential associations between dietary patterns, foods nutrients and NIDDM initiation.…”
Section: Introductionmentioning
confidence: 99%